O sistema nacional de pesquisa agropecuária: Histórico, estrutura e financiamento - Caroline Nascimento Pereira; César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This article makes an evaluation of the history, structure and financing of the Brazilian agricultural research, evaluating the transfers from the Federal Government to Embrapa and, mainly, the values to CT-Agro, the sectorial fund created to promoting R&D activities related to this sector. The goal is to verify the current constitution of the SNPA and the participation of the sectorial fund for the promotion of innovation in the agricultural sector. In order to do so, the paper analyses the evolution over the years of the SNPA, which includes a diversity of agents that act in networks, with a capacity to interfere in the process of innovation and research. It was observed that the system is well structured and strongly dependent on public resources focused mainly on basic and applied research, carried out via Embrapa or sectoral funds. CT-Agro has small expressive participation in the research structure, but significant importance for market signaling of the government's performance in agricultural R&D.
Keywords: O13; O3; O38; 330; agriculture; SNPA; sectorial funds; CT-Agro